Hypertension in renal allograft recipients may be conveyed by cadaveric kidneys from donors with subarachnoid haemorrhage. Issue 6527 (19th April 1986) - Strandgaard, S; Hansen, U
Abstract : Evidence for hypertension was sought retrospectively in the necropsy records of 37 cadaveric kidney donors who had died of subarachnoid haemorrhage and 41 donors who had died of head injury, cerebral tumour, or (in a few instances) other causes. Mean relative heart weight in the donors with subarachnoid haemorrhage was 0.58 (1 SD = 0.09)% and in the other donors 0.52 (0.09)% (p less than 0.01), a difference unexplained by any factor other than a comparatively higher blood pressure in the donors who had died of subarachnoid haemorrhage. Blood pressure was analysed over 72 months after renal transplantation in 23 recipients with normal or near normal graft function and no evidence of chronic rejection or graft artery stenosis. Twelve patients who had received kidneys from donors with subarachnoid haemorrhage had consistently higher systolic blood pressures (p less than 0.004) and needed more antihypertensive treatment (p less than 0.0004) than the 11 recipients of kidneys from donors who had died of head injury or cerebral tumour. These observations suggest that cadaveric kidneys from donors dying of subarachnoid haemorrhage may induce or sustain hypertension after transplantation.